Globalisation, de-globalisation, re-globalisation. On old globalisation, de-globalisation pre- and under Corona, and the restructuring of VACs 'post-Corona'. (4th October 2021) - Elsner, Wolfram
We analyse 'old' globalisation as a process that endogenously lead into global troubles. 'Old' globalisation, from some point, thus was paradoxically characterised by reactive de-globalisations. Also the USA, against a reverted cost-benefit relation from globalisation for itself, changed its strategy and politically accelerated already ongoing de-globalisations. COVID-19 has further reinforced de-globalisation by interrupting international value-added chains (IVACs), and the Trump administration acted to further 'decouple' international relations (not only with China). However, forms of rebuilding and restructuring IVACs are under way, e.g., through China's fast recovery and development. This will find China's initiative of 'Belt&Road' as a new dimension of global trade structures. It is discussed whether there will be a disintegration into two economic blocs or whether a renewed multilateralism and a new global deal on trade and VACs, including inequality, climate change, and global health, will be feasible. This 'turn of the tide' provides a time window for heterodox economics and education.